All-solid-state flexible ultrathin micro-supercapacitors based on graphene - Niu, Zhiqiang (2014)
Flexible, compact, ultrathin and all-solid-state micro-supercapacitors are prepared by coating H3PO4/PVA gel electrolyte onto micro-patterned rGO interdigitated electrodes prepared by combining photolithography with selective electrophoretic deposition.